Torts of public nuisance and the environmental laws on public nuisance in Malaysia: a comparative study / Nur Fadrina Zulkhairi, Siti Fatimah Alimuddin - Zulkhairi, Nur Fadrina; Alimuddin, Siti Fatimah (2008)
This project paper is concerning on the present status on laws of public nuisance in Malaysia. Despite tremendous laws existed in Malaysia, yet we witness substantial phenomenon of public nuisance occurred. The research conducted are only limited to tortious laws on public nuisance, the provisions on public nuisance under Environmental Quality Act which is limited to industrial waste management and the Local Government Act. This project paper will touch on these laws and its components. Therefore a comparative study will be done in determining the strength and weaknesses of these laws. In addition, this research paper will also include a case study in order to determine the practicability and the effectiveness of these laws. In the end of this project paper, recommendations will be proposed based on the findings of the research with the hope to increase effectiveness of the laws on public nuisance.